2021
DOI: 10.15255/cabeq.2020.1872
|View full text |Cite
|
Sign up to set email alerts
|

Removal Efficiency of Textile Dyes from Aqueous Solutions Using Calcined Waste of Eggshells as Eco-friendly Adsorbent

Abstract: This research investigates the removal of textile dyes (Rhodamine B and Alizarin Red S) from aqueous solution by a low-cost adsorbent prepared from eggshell waste. Batch adsorption experiments were conducted in order to determine the effect of different parameters such as pH, dye concentration, contact time, adsorbent dosage, particle <br /> size, and temperature. The best correlation was found by Langmuir model, and the maximum adsorption capacity was 175.58 mg g–1 for Rhodamine B and 156.56 mg g–1 for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…These pores gave room for the adsorption of arsenic. The results of the scanning electron microscope, backscattered electron detector and secondary electron detector are as presented in figures 3-9 present similar micrograph structures of eggshells from literature such as Ajala et al, (2018), Slimani et al, (2021), Kuh and Kim (2000); Elkady et al, (2011);Tsai et al, (2006); Zulfikar et al, (2012), Hess et al, (2018), Smirnova et al, (2016), Lin et al, (2020) and Krzytof et al, (2017), which established the composition and structure of eggshells. The results revealed that the PWDEs is a calcite material (calcium salt).…”
Section: The Composition Of the Pwdes And Adsorption Mechanismsupporting
confidence: 74%
See 1 more Smart Citation
“…These pores gave room for the adsorption of arsenic. The results of the scanning electron microscope, backscattered electron detector and secondary electron detector are as presented in figures 3-9 present similar micrograph structures of eggshells from literature such as Ajala et al, (2018), Slimani et al, (2021), Kuh and Kim (2000); Elkady et al, (2011);Tsai et al, (2006); Zulfikar et al, (2012), Hess et al, (2018), Smirnova et al, (2016), Lin et al, (2020) and Krzytof et al, (2017), which established the composition and structure of eggshells. The results revealed that the PWDEs is a calcite material (calcium salt).…”
Section: The Composition Of the Pwdes And Adsorption Mechanismsupporting
confidence: 74%
“…The laboratory analyses of pH and arsenic ion concentrations in both synthetic and natural water used were conducted as specified in APHA (Rice and Bridgewater, 2012). Thermodynamic parameters (enthalpy, ΔH o , entropy, ΔS o , and free Gibbs energy ΔG o ) of adsorption kinetics of A se onto PWDES were computed using Microsoft Excel Solver based on experiments performance in a batch system at time between 1 and 12 hours as follows (Devi and Mishra, 2019;Slimani et al, 2021;Singh and Pant, 2004): R is the universal gas constant (8.314 J mol -1 k -1 ), T is the temperature (303K). K d is the distribution coefficient.…”
Section: Determination Of Adsorption Performance Of the Pwdesmentioning
confidence: 99%